RANCANG BANGUN APLIKASI BEHAVIOR BASED SAFETY QUESTIONNAIRE DI PT INFINEON TECHNOLOGIES BATAM - Supardianto; Gabriella Joice Sitompul, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Infineon Technologies Batam is a company operating in the semiconductor sector, specifically engaged in IC production. In an effort to reduce paper usage, the company has implemented a paperless program. Additionally, PT. Infineon Technologies Batam has established a data protection system to prevent data leaks, utilizing an intranet network that restricts access to certain websites, such as Google Forms. The company's Environmental, Safety & Health (ESH) department has developed a work program aimed at providing comprehensive knowledge of K3 (Environmental, Safety, and Health) material to all employees. To monitor the effectiveness of this program, the ESH department has proposed the implementation of an EHS questionnaire. This questionnaire will adhere to the material standards set by the ESH department and will be distributed to each employee. To facilitate this process without the need for paper, the ESH department has requested the development of a web-based questionnaire application. In response, the authors have created and developed a BBS (Behavior Safety) Questionnaire application using the C# programming language and the ASP.NET Framework. The BBS Questionnaire database is managed using SQL Server.